Availability of complementary resources and equipment for use in the prevention of healthcare-associated infections - Figueiredo Veríssimo, Pérola (2023)
Background and Objectives: Recently, complementary resources and equipment have emerged to improve prevention of healthcare-associated infections (HAIs). Our aim is to verify availability and use of different resources/equipment by infection controllers. Methods: We conducted a survey with infection controllers from the State of Rio de Janeiro, Brazil, by invitation using a social media group, in August 2022. Nine different resources and equipment were evaluated. Categorical and continuous variables were evaluated by the chi-square test and Mann–Whitney U test, respectively. A p value of less than 0.05 was considered statistically significant. Results: One hundred and eight persons answered the questionnaire. The mean age was 42.8 years (SD +/- 8.5 years) and 53 (49.1%) reported most of their workload in public hospitals, 45 (41.7%) in private hospitals and 10 (9.2%) reported the same workload in public and private hospitals. Sixty-there percent reported teaching activities in their institutions. There was no correlation between the existence of teaching activities and hospital profile (p=0.42). The most common resource available was molecular biology (PCR) for microbiological samples research for 73 (67.6%) participants. The second resource most available was applications (Apps) for HAIs prevention and control for 33 (30.6%), 19 (17.6%) reported no availability of resource/equipment technology. Conclusion: Molecular biology (PCR) for microbiological samples research was the most common resource available for infection controllers of an important state of Brazil.